Silent Sinus Syndrome and Williams Syndrome: Two Rare Diseases Found in a Pediatric Patient - Maddalena Petraroli; Sara Riscassi; Arianna Panigari; Marilena Maltese; Susanna Esposito (Frontiers Media S.A., 2020)
Silent sinus syndrome (SSS) is a rare disease process characterized by progressive enophthalmos and hypoglobus due to ipsilateral maxillary sinus hypoplasia and orbital floor resorption. Patients may also present with eye asymmetry, unilateral ptosis, or diplopia. Most reported cases in the literature describe its occurrence in adults, but it can also affect children. The etiology remains speculative, even though the most accepted theory is that during the first or second decade of life, occlusion of the maxillary ostium causes an interruption in normal sinus development. Williams syndrome (WS) is a rare genetic, multisystem disorder characterized by a constellation of distinctive phenotypic features, including psychomotor delay and cardiovascular abnormalities. We report a case of a 7-year-old female diagnosed at 1 year old with WS and who gradually developed SSS. This last condition was diagnosed at 7 years of age, when she started showing progressive facial asymmetry in addition to typical facial features of WS; subsequent neuroimaging definitively supported the diagnosis. This case report describes for the first time in the literature an uncommon situation in which SSS and WS, both rare syndromes, are present in the same pediatric patient. We speculate that the particular facial features typical of WS could either be the basis of the development of SSS in our patient or make the SSS clinical course more severe, with signs presenting at the age of 7 years. This case report shows for the first time that facial asymmetry in WS can be caused by SSS and highlights the need for early identification of this complication in patients with syndromes characterized by dysmorphic facial features. Further studies are needed to understand whether there is a link between the two syndromes as well as to evaluate the prevalence of SSS in patients with facial dysmorphisms and define the best management.